RANKL pretreatment plays an important role in the differentiation of pit-forming osteoclasts induced by TNF-α on murine bone marrow macrophages. Issue 9 (September 2015) - Yamashita, Yasunori; Ukai, Takashi; Nakamura, Hirotaka; Yoshinaga, Yasunori; Kobayashi, Hiroki; Takamori, Yuzo; Noguchi, Satoshi; Yoshimura, Atsutoshi; Hara, Yoshitaka
Highlights We examined the condition of acceleration of osteoclast formation by TNF-α. We checked whether TNF-α after RANKL pretreatment could promote resorbing activity. TNF-α after 10 ng/mL RANKL pretreatment significantly promoted osteoclast formation. TNF-α after 10 ng/mL RANKL pretreatment dynamically generated pit-forming osteoclasts. The effects of TNF-α after RANKL pretreatment might be independent of RANKL.